The impact of electronic information resources on academic research: A case study of Kaduna Polytechnic - Bappah, Hauwa Usman; Abd Wahab, Alawiyah (2017)
Purpose - With advancement of Information and Communication Technology (ICT) and Internet, e-resources have become influential tools to educational information by spreading high-tech knowledge and giving individuals everywhere fast access to enormous resources.With the proliferation of e-resources around the globe, there is an increase in usage of the resources for research and other educational purposes. A study to assess the effect of e-resources on the academicians is vital so as to ascertain the extent of usage and the impact e-resources has on their scholarly work. Although there have been a number of studies that discussed the impact of e-resources use in the universities worldwide, the research on the impact of e-resources usage on productivity of academician is quite low. This study sought to address these issues by exploring the perceived effect of electronic resources usage on the lecturers in their literature search for professional growth by and large and the institution’s academic excellence for the teaching, learning and research.Specifically the objectives of this study are (1) to determine the pattern of e-resources usage by academicians, (2) to examine the perceived impact of e-resources usage on the academicians’ research.